The RNA polymerase II CTD coordinates transcription and RNA processing - Hsin, Jing-Ping (Cold Spring Harbor Laboratory Press, 2012)
The C-terminal domain (CTD) of the RNA polymerase II largest subunit consists of multiple heptad repeats (consensus Tyr1–Ser2–Pro3–Thr4–Ser5–Pro6–Ser7), varying in number from 26 in yeast to 52 in vertebrates. The CTD functions to help couple transcription and processing of the nascent RNA and also plays roles in transcription elongation and termination. The CTD is subject to extensive post-translational modification, most notably phosphorylation, during the transcription cycle, which modulates its activities in the above processes. Therefore, understanding the nature of CTD modifications, including how they function and how they are regulated, is essential to understanding the mechanisms that control gene expression. While the significance of phosphorylation of Ser2 and Ser5 residues has been studied and appreciated for some time, several additional modifications have more recently been added to the CTD repertoire, and insight into their function has begun to emerge. Here, we review findings regarding modification and function of the CTD, highlighting the important role this unique domain plays in coordinating gene activity.